Negative photoresist composition and patterning method

By using specific polymers and other additives in the negative photoresist composition, the molar proportion and molecular weight distribution are optimized, and the bridging, substrate dependence and undercut problems of traditional photoresist in fine pattern formation are solved, thereby achieving high sensitivity and high resolution pattern formation.

CN119781248APending Publication Date: 2025-04-08FUYANG SINEVA MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411993778.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When forming fine patterns of 0.1 μm and smaller sizes, there are problems such as bridging, strong substrate dependence and difficulty in achieving high resolution. The undercutting problem is particularly serious when using substrates such as chromium nitride oxide.

Method used

A novel negative photoresist composition is used, which includes specific polymers, acid generators, carboxyl-containing amine compounds, crosslinking agents, surfactants and solvents, and the mole ratio and molecular weight distribution of the polymer are optimized to improve the performance of the composition.

Benefits of technology

The negative photoresist composition reduces the bridging and substrate dependence when forming patterns, achieves high sensitivity and high resolution, can meet the needs of forming finer patterns, and improves etch resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119781248A_ABST
    Figure CN119781248A_ABST
Patent Text Reader

Abstract

The invention provides a negative photoresist composition and a patterning method, the negative photoresist composition comprises a polymer, and the polymer comprises a first repeating unit as shown in a formula (1) and a second repeating unit as shown in a formula (2); # imgabs0 # wherein m and n are independently selected from an integer from 1 to 4, and X includes an electron donating group. The negative photoresist composition provided by the invention is difficult to bridge when forming a pattern, low in substrate dependence, capable of obtaining high sensitivity and high resolution, and capable of meeting the formation requirement of a finer pattern.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photoresists, and in particular to a negative photoresist composition and a patterning method. Background Art

[0002] In recent years, with the rapid development of integrated circuit technology, high integration has become one of the main goals in this field, which has directly led to the continuous improvement of the requirements for patterning technology. In particular, when forming precise resist patterns with a size below 0.2μm, traditional photolithography technology has been unable to meet the requirements.

[0003] As pattern sizes continue to shrink to 0.1μm or even smaller, traditional negative photoresist compositions have difficulty meeting performance requirements. For example, bridging (i.e., filamentary resist layers remain between fine pattern lines) and pattern substrate dependence (i.e., changes in pattern profiles near the substrate due to differences in substrate materials to be processed) are becoming increasingly prominent. Undercutting is particularly serious when using specific substrates such as chromium oxynitride, and as patterns become miniaturized, even small profile changes can have a significant impact on device performance.

[0004] Existing negative photoresist compositions are still inadequate for finer patterns (especially negative photoresist films with a thickness of less than 100 nm). In practical applications, problems such as the collapse of fine patterns, bridging between pattern lines, and the inability to achieve high resolution still plague technicians.

[0005] Therefore, as integrated circuit technology continues to develop towards higher integration, how to further optimize negative photoresist compositions to meet the needs of forming finer patterns has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present application is to provide a negative photoresist composition and a patterning method to solve the above problems.

[0007] To achieve the above objectives, this application adopts the following technical solutions:

[0008] A negative photoresist composition, comprising a polymer, wherein the polymer comprises a first repeating unit represented by formula (1) and a second repeating unit represented by formula (2);

[0009]

[0010] wherein m and n are independently selected from integers of 1 to 4, and X comprises an electron donating group.

[0011] According to an embodiment of the present application, each of the Xs is independently selected from any one of a hydrogen atom, a linear alkyl group, a branched alkyl group or a cyclic alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms;

[0012] Preferably, each X is independently selected from any one of methyl, ethyl, methoxy and ethoxy.

[0013] According to an embodiment of the present application, the polymer further comprises a third repeating unit represented by formula (3);

[0014]

[0015] The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the third repeating unit in the polymer is 8% to 12%.

[0016] According to an embodiment of the present application, the polymer further comprises a fourth repeating unit represented by formula (4);

[0017]

[0018] The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the fourth repeating unit in the polymer is 8% to 12%.

[0019] According to an embodiment of the present application, the weight average molecular weight of the polymer is 1,000 to 10,000.

[0020] According to an embodiment of the present application, the negative photoresist composition further includes an acid generator, a carboxyl-containing amine compound, a crosslinking agent, a surfactant, and a solvent, wherein the nitrogen atom in the carboxyl-containing amine compound is not connected to a hydrogen atom.

[0021] According to an embodiment of the present application, the acid generator includes triphenylsulfonium-2,4,6-triisopropylbenzenesulfonate;

[0022] The carboxyl-containing amine compounds include p-diethylaminobenzoic acid and 1-piperidinylpropionic acid;

[0023] The cross-linking agent includes tetramethoxymethyl glycoluril;

[0024] The surfactant includes PF-636;

[0025] The solvents include ethyl lactate and propylene glycol methyl ether acetate.

[0026] According to an embodiment of the present application, in the negative photoresist composition, the mass ratio of the polymer to the acid generator is 80:(8~12), the mass ratio of the polymer to the p-diethylaminobenzoic acid is 80:(0.05~0.15), the mass ratio of the polymer to the 1-piperidinepropionic acid is 80:(0.05~0.15), the mass ratio of the polymer to the cross-linking agent is 80:(6~10), the mass ratio of the polymer to the surfactant is 80:(0.05~0.09), and the mass ratio of the polymer to the solvent is 80:(2400~2800).

[0027] The present application also provides a patterning method, comprising:

[0028] Applying the negative photoresist composition described above on the substrate to be processed to form a negative photoresist layer;

[0029] performing an exposure process on the negative photoresist layer;

[0030] The negative photoresist layer subjected to the exposure treatment is developed to obtain a resist pattern.

[0031] According to an embodiment of the present application, the thickness of the negative photoresist layer is 10-100 nm;

[0032] And / or, the substrate to be processed includes a photomask blank, and the outer surface material of the photomask blank includes a chromium-containing compound.

[0033] Compared with the prior art, the beneficial effects of this application include:

[0034] The negative photoresist composition and patterning method of the present application are unlikely to cause bridging when forming a pattern, have low substrate dependence, and can achieve high sensitivity and high resolution, thereby meeting the requirements for forming finer patterns. DETAILED DESCRIPTION

[0035] As used herein:

[0036] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0037] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0038] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0039] In these examples, parts and percentages are by mass unless otherwise indicated.

[0040] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0041] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0042] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0043] A negative photoresist composition, comprising a polymer, wherein the polymer comprises a first repeating unit represented by formula (1) and a second repeating unit represented by formula (2);

[0044]

[0045] wherein m and n are independently selected from integers of 1 to 4, and X comprises an electron donating group.

[0046] According to an embodiment of the present application, each of the Xs is independently selected from any one of a hydrogen atom, a linear alkyl group, a branched alkyl group or a cyclic alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms;

[0047] Preferably, each X is independently selected from any one of methyl, ethyl, methoxy and ethoxy.

[0048] The polymer of the present application has the following characteristics: the polymer is soluble in an alkaline environment, but becomes alkali-insoluble in an acidic environment, or the polymer can react with a cross-linking agent under acidic conditions and then be converted into an alkali-insoluble state.

[0049] According to an embodiment of the present application, the polymer further comprises a third repeating unit represented by formula (3);

[0050]

[0051] The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the third repeating unit in the polymer is 8% to 12%.

[0052] For example, the molar proportion of the first repeating unit in the polymer can be 73%, 74%, 75%, 76%, 76.7%, 77%, 78%, 79%, 80% or any value between 73% and 80%, the molar proportion of the second repeating unit in the polymer can be 10%, 11%, 12%, 12.5%, 13%, 14%, 15% or any value between 10% and 15%, and the molar proportion of the third repeating unit in the polymer can be 8%, 9%, 10%, 10.8%, 11%, 12% or any value between 8% and 12%.

[0053] When the polymer contains the third repeating unit, it is beneficial to improve the etching resistance of the negative photoresist composition, thereby obtaining a thinner negative photoresist film.

[0054] According to an embodiment of the present application, the polymer further comprises a fourth repeating unit represented by formula (4);

[0055]

[0056] The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the fourth repeating unit in the polymer is 8% to 12%.

[0057] For example, the molar proportion of the first repeating unit in the polymer can be 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80% or any value between 73% and 80%, the molar proportion of the second repeating unit in the polymer can be 10%, 11%, 12%, 12.5%, 13%, 14%, 15% or any value between 10% and 15%, and the molar proportion of the fourth repeating unit in the polymer can be 8%, 9%, 10%, 10.5%, 11%, 12% or any value between 8% and 12%.

[0058] When the polymer contains the fourth repeating unit, it is beneficial to improve the etching resistance of the negative photoresist composition, thereby obtaining a thinner negative photoresist film.

[0059] According to an embodiment of the present application, the weight average molecular weight of the polymer is 1,000 to 10,000.

[0060] For example, the weight average molecular weight of the polymer may be 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 or any value between 1000 and 10000. The weight average molecular weight of the polymer is preferably between 1000 and 5000.

[0061] According to some embodiments of the present application, the polymer is prepared by pouring acetoxystyrene, 4-methoxystyrene, a polycyclic compound and toluene into a flask. The reaction vessel is cooled to -70°C under a nitrogen atmosphere, and the decompression degassing and nitrogen flow are repeated three times. After warming to room temperature, 2.2'-azobis(2,4-dimethylvaleronitrile): V-65 is added as a polymerization initiator, and the temperature is raised to 45°C, reacted for 20 hours, and then raised to 55°C, and reacted for another 20 hours. The reaction solution is then concentrated to 1 / 2 and precipitated in a methanol solution; the obtained solid is filtered and then dried under reduced pressure at 40°C to obtain a first intermediate. The first intermediate is dissolved again in a mixture of methanol and tetrahydrofuran, and then triethylamine and water are added, and a deprotection reaction is carried out at 60°C for 40 hours. As a fractionation step, the reaction solution is concentrated, dissolved in a mixed solvent of methanol and acetone, and then hexane is added dropwise to the solution within 10 minutes. The mixed white turbid solution is allowed to stand for stratification, and the lower layer (second intermediate layer) is concentrated. The condensed second intermediate is further dissolved in a mixture of methanol and acetone again, and the solution is dispersed and separated using hexane, and the obtained lower layer (third intermediate layer) is concentrated. The concentrated solution is dissolved in ethyl acetate, and then neutralized and separated and washed once with a mixture of water and acetic acid, and then separated and washed once with water and pyridine, and then separated and washed four times with water. Then, the upper ethyl acetate solution is concentrated, dissolved in acetone, precipitated in water, filtered, and vacuum dried at 50°C for 40 hours to obtain a polymer. Among them, the polycyclic compound includes indene or acenaphthene.

[0062] According to an embodiment of the present application, the negative photoresist composition further includes an acid generator, a carboxyl-containing amine compound, a crosslinking agent, a surfactant, and a solvent, wherein the nitrogen atom in the carboxyl-containing amine compound is not connected to a hydrogen atom.

[0063] When the polymer of the present application is combined with a carboxyl-containing amine compound, the problems of bridging and undercutting between fine patterns can be significantly improved.

[0064] According to an embodiment of the present application, the acid generator includes triphenylsulfonium-2,4,6-triisopropylbenzenesulfonate;

[0065] The carboxyl-containing amine compounds include p-diethylaminobenzoic acid and 1-piperidinylpropionic acid;

[0066] The cross-linking agent includes tetramethoxymethyl glycoluril;

[0067] The surfactant includes PF-636;

[0068] The solvents include ethyl lactate and propylene glycol methyl ether acetate.

[0069] According to an embodiment of the present application, in the negative photoresist composition, the mass ratio of the polymer to the acid generator is 80:(8~12), the mass ratio of the polymer to the p-diethylaminobenzoic acid is 80:(0.05~0.15), the mass ratio of the polymer to the 1-piperidinepropionic acid is 80:(0.05~0.15), the mass ratio of the polymer to the cross-linking agent is 80:(6~10), the mass ratio of the polymer to the surfactant is 80:(0.05~0.09), and the mass ratio of the polymer to the solvent is 80:(2400~2800).

[0070] For example, in the negative photoresist composition, the mass ratio of the polymer to the acid generator can be 80:8, 80:9, 80:10, 80:11, 80:12 or any value between 80:(8-12); the mass ratio of the polymer to p-diethylaminobenzoic acid can be 80:0.05, 80:0.1, 80:0.15 or any value between 80:(0.05-0.15); the mass ratio of the polymer to 1-piperidinylpropionic acid can be 80:0.05, 80:0.1, 80:0.15 or any value between 80:(0.05-0.15); the mass ratio of the polymer to the crosslinking agent can be 80:0.05, 80:0.1, 80:0.15 or any value between 80:(0.05-0.15); The mass ratio can be 80:6, 80:7, 80:8, 80:8.2, 80:9, 80:10 or any value between 80:(6-10); the mass ratio of polymer to surfactant can be 80:0.05, 80:0.06, 80:0.07, 80:0.08, 80:0.09 or any value between 80:(0.05-0.09); the mass ratio of polymer to solvent can be 80:2400, 80:2500, 80:2600, 80:2700, 80:2800 or any value between 80:(2400-2800).

[0071] The present application also provides a patterning method, comprising:

[0072] Applying the negative photoresist composition described above on the substrate to be processed to form a negative photoresist layer;

[0073] performing an exposure process on the negative photoresist layer;

[0074] The negative photoresist layer subjected to the exposure treatment is developed to obtain a resist pattern.

[0075] Further, performing the exposure process includes performing high energy beam exposure.

[0076] Furthermore, the developer used for development is an alkaline developer.

[0077] According to an embodiment of the present application, the thickness of the negative photoresist layer is 10-100 nm;

[0078] For example, the thickness of the negative photoresist layer may be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value between 10-100 nm.

[0079] And / or, the substrate to be processed includes a photomask blank, and the outer surface material of the photomask blank includes a chromium-containing compound.

[0080] According to some embodiments of the present application, the chromium-containing compound includes chromium oxynitride.

[0081] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0082] Synthesis example 1

[0083] 238.0 g of 4-acetoxystyrene, 22.6 g of 4-methoxystyrene, 189.4 g of indene and 675 g of toluene as a solvent were poured into a 3 L flask. The reaction vessel was cooled to -70 ° C under a nitrogen atmosphere, and the decompression degassing and nitrogen flow were repeated three times. After warming to room temperature, 40.5 g of 2.2'-azobis (2,4-dimethylvaleronitrile): V-65 was added as a polymerization initiator, and the temperature was raised to 45 ° C, reacted for 20 hours, and then raised to 55 ° C, and reacted for another 20 hours. The reaction solution was then concentrated to 1 / 2 and precipitated in 15 L of methanol solution; the obtained white solid was filtered and then dried under reduced pressure at 40 ° C to obtain 311 g of white polymer. The polymer was dissolved again in a mixture of 488 g of methanol and 540 g of tetrahydrofuran, and then 162 g of triethylamine and 32 g of water were added, and the deprotection reaction was carried out at 60 ° C for 40 hours. As a fractionation step, the reaction solution was concentrated and dissolved in a mixed solvent of 548g methanol and 112g acetone, and then 990g hexane was added dropwise to the solution within 10 minutes. The mixed white turbid solution was allowed to stand for stratification, and the lower layer (polymer layer) was taken out and concentrated. The condensed polymer was further dissolved in a mixed solvent of 548g methanol and 112g acetone, and the solution was dispersed and separated using 990g hexane, and the obtained lower layer (polymer layer) was concentrated. The concentrated solution was dissolved in 870g ethyl acetate, and then neutralized and separated and washed once with a mixed solution of 250g water and 98g acetic acid, and then separated and washed once with 225g water and 75g pyridine, and then separated and washed four times with 225g water. Then, the upper ethyl acetate solution was concentrated, dissolved in 250g acetone, precipitated in 15L water, filtered, and vacuum dried at 50°C for 40 hours to obtain 187g of white polymer.

[0084] The obtained polymer was 13 C. 1 H-NMR and GPC measurements gave the following analysis results: the polymer includes a first repeating unit (m=1) as shown in formula (1), a second repeating unit (X is methoxy, n=1) as shown in formula (2), and a third repeating unit as shown in formula (3); the copolymer composition ratio (molar ratio) is: first repeating unit (hydroxystyrene): second repeating unit (4-methoxystyrene): third repeating unit (indene) = 76.7:12.5:10.8; weight average molecular weight (Mw) = 4200; molecular weight distribution (Mw / Mn) = 1.59; the polymer obtained in Example 1 is referred to as polymer-1.

[0085] Synthesis example 2

[0086] 222.0g of acetoxystyrene, 32.6g of 4-methoxystyrene, 30.0g of acenaphthene and 675g of toluene were poured into a 3L flask as solvent. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and the decompression degassing and nitrogen flow were repeated three times. After warming to room temperature, 40.1g of 2.2'-azobis(2,4-dimethylvaleronitrile):V-65 was added as a polymerization initiator, and the temperature was raised to 45°C, reacted for 20 hours, and then raised to 55°C, and reacted for another 20 hours. The reaction solution was then concentrated to 1 / 2 and precipitated in 15.0L of methanol solution; the obtained white solid was filtered and then dried under reduced pressure at 40°C to obtain 299g of white polymer. The polymer was dissolved again in a mixture of 488g of methanol and 540g of tetrahydrofuran, and then 162g of triethylamine and 32g of water were added, and the deprotection reaction was carried out at 60°C for 40 hours. As a fractionation step, the reaction solution was concentrated and dissolved in a mixed solvent of 548g methanol and 112g acetone, and then 990g hexane was added dropwise to the solution within 10 minutes. The mixed white turbid solution was allowed to stand for stratification, and the lower layer (polymer layer) was concentrated. The condensed polymer was further dissolved in a mixture of 548g methanol and 112g acetone, and the solution was dispersed and separated using 990g hexane, and the obtained lower layer (polymer layer) was concentrated. The concentrated solution was dissolved in 870g ethyl acetate, and then neutralized and separated and washed once with a mixed solution of 250g water and 98g acetic acid, and then separated and washed once with 225g water and 75g pyridine, and then separated and washed four times with 225g water. Then, the upper ethyl acetate solution was concentrated, dissolved in 250g acetone, precipitated in 15L water, filtered, and vacuum dried at 50°C for 40 hours to obtain 165g white polymer.

[0087] The obtained polymer was 13 C. 1 H-NMR and GPC measurements gave the following analysis results: the polymer includes a first repeating unit (m=1) as shown in formula (1), a second repeating unit (X is methoxy, n=1) as shown in formula (2), and a fourth repeating unit as shown in formula (4); the copolymer composition ratio (molar ratio) is: first repeating unit (hydroxystyrene): second repeating unit (4-methoxystyrene): fourth repeating unit (acenaphthene) = 77.0:12.5:10.5; weight average molecular weight (Mw) = 4700; molecular weight distribution (Mw / Mn) = 1.63; the polymer obtained in Example 2 is referred to as polymer-2.

[0088] Comparative Synthesis Example 1

[0089] 354.4 g of acetoxystyrene, 94.6 g of 4-chlorostyrene and 1500 g of toluene as solvent were poured into a 3L flask. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassing under reduced pressure and nitrogen flow were repeated three times. After heating to room temperature, 23.6 g of AIBN was added as a polymerization initiator, and the temperature was raised to 65°C and reacted for 40 hours. The reaction solution was then concentrated to 1 / 2 and precipitated in 20.0 L of methanol solution; the obtained white solid was filtered and then dried under reduced pressure at 40°C to obtain 420 g of white polymer. The polymer was dissolved again in a mixture of 488 g of methanol and 540 g of tetrahydrofuran, and then 162 g of triethylamine and 32 g of water were added, and a deprotection reaction was carried out at 60°C for 40 hours. As a fractionation step, the reaction solution was concentrated and dissolved in a mixed solvent of 822 g of methanol and 168 g of acetone, and then 1485 g of hexane was added dropwise to the solution within 10 minutes. The mixed white turbid solution was allowed to stand for stratification, and the lower layer (polymer layer) was concentrated. The condensed polymer was further dissolved again in a mixture of 822 g methanol and 168 g acetone, and the solution was dispersed and separated using 1485 g hexane, and the obtained lower layer (polymer layer) was concentrated. The concentrated solution was dissolved in 1300 g ethyl acetate, and then neutralized and separated and washed once with a mixed solution of 375 g water and 98 g acetic acid, and further separated and washed once with 375 g water and 75 g pyridine, and separated and washed four times with 225 g water. Then, the upper ethyl acetate solution was concentrated, dissolved in 375 g acetone, precipitated in 20 L water, filtered, and vacuum dried at 50 ° C for 40 hours to obtain 280 g of white polymer.

[0090] The obtained polymer was 13 C. 1 H-NMR and GPC measurements gave the following analysis results: the polymer included a first repeating unit (m=1) as shown in formula (1) and a second repeating unit (X is an electron withdrawing group, specifically chlorine, and n=1) as shown in formula (2); the copolymer composition ratio (molar ratio) was as follows: first repeating unit (hydroxystyrene): second repeating unit (4-chlorostyrene) = 76.8:23.2; weight average molecular weight (Mw) = 5200; molecular weight distribution (Mw / Mn) = 1.62; the polymer obtained by comparison with Synthesis Example 1 was referred to as Polymer-3.

[0091] Comparative Synthesis Example 2

[0092] 238.0g of acetoxystyrene, 22.6g of 4-chlorostyrene, 189.4g of indene and 675g of toluene were poured into a 3L flask as solvent. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and the decompression degassing and nitrogen flow were repeated three times. After warming to room temperature, 40.5g of 2.2'-azobis(2,4-dimethylvaleronitrile):V-65 was added as a polymerization initiator, and the temperature was raised to 45°C, reacted for 20 hours, and then raised to 55°C, and reacted for another 20 hours. The reaction solution was then concentrated to 1 / 2 and precipitated in 15.0L of methanol solution; the obtained white solid was filtered and then dried under reduced pressure at 40°C to obtain 311g of white polymer. The polymer was dissolved again in a mixture of 488g of methanol and 540g of tetrahydrofuran, and then 162g of triethylamine and 32g of water were added, and the deprotection reaction was carried out at 60°C for 40 hours. As a fractionation step, the reaction solution was concentrated and dissolved in a mixed solvent of 548g methanol and 112g acetone, and then 990g hexane was added dropwise to the solution within 10 minutes. The mixed white turbid solution was allowed to stand for stratification, and the lower layer (polymer layer) was taken out and concentrated. The condensed polymer was further dissolved in a mixed solvent of 548g methanol and 112g acetone, and the solution was dispersed and separated using 990g hexane, and the obtained lower layer (polymer layer) was concentrated. The concentrated solution was dissolved in 870g ethyl acetate, and then neutralized and separated and washed once with a mixed solution of 250g water and 98g acetic acid, and then separated and washed once with 225g water and 75g pyridine, and then separated and washed four times with 225g water. Then, the upper ethyl acetate solution was concentrated, dissolved in 250g acetone, precipitated in 15L water, filtered, and vacuum dried at 50°C for 40 hours to obtain 187g of white polymer.

[0093] The obtained polymer was 13 C. 1 H-NMR and GPC measurements gave the following analysis results: the polymer includes a first repeating unit (m=1) as shown in formula (1), a second repeating unit (X is an electron withdrawing group, specifically chlorine, n=1) as shown in formula (2), and a third repeating unit as shown in formula (3); the copolymer composition ratio (molar ratio) is: first repeating unit (hydroxystyrene): second repeating unit (4-chlorostyrene): third repeating unit (indene) = 76.0:6.5:17.5; weight average molecular weight (Mw) = 4200; molecular weight distribution (Mw / Mn) = 1.59; the polymer obtained by comparison with Synthesis Example 2 is referred to as polymer-4.

[0094] Example 1

[0095] Example 1 provides a negative photoresist composition, including: the polymer prepared in Synthesis Example 1, as well as an acid generator, p-diethylaminobenzoic acid (Quencher-1), 1-piperidinepropionic acid (Quncher-2), a crosslinking agent, a surfactant, and a solvent.

[0096] Among them, the acid generator is triphenylsulfonium-2,4,6-triisopropylbenzenesulfonate (PAG), the cross-linking agent is tetramethoxymethyl glycoluril, the surfactant is PF-636, the solvents are propylene glycol methyl ether acetate (solvent A) and ethyl lactate (solvent B), the mass ratio of the polymer to the acid generator is 80:10, the mass ratio of the polymer to p-diethylaminobenzoic acid is 80:0.1, the mass ratio of the polymer to 1-piperidinepropionic acid is 80:0.1, the mass ratio of the polymer to the cross-linking agent is 80:8.2, the mass ratio of the polymer to the surfactant is 80:0.07, and the mass ratio of the polymer to the solvent is 80:2600.

[0097] Example 2

[0098] The other components of the negative photoresist composition in Example 2 are the same as those in Example 1, except that the polymer in Example 2 is the polymer prepared in Synthesis Example 2.

[0099] Comparative Example 1

[0100] The other components of the negative photoresist composition in Comparative Example 1 are the same as those in Example 1, except that the polymer in Comparative Example 1 is the polymer prepared in Comparative Synthesis Example 1.

[0101] Comparative Example 2

[0102] The other components of the negative photoresist composition in Comparative Example 2 are the same as those in Example 1, except that the polymer in Comparative Example 2 is the polymer prepared in Comparative Synthesis Example 2.

[0103] The specific compositions of the negative photoresist compositions of Example 1-2 and Comparative Example 1-2 are shown in Table 1.

[0104] Table 1 Specific composition of negative photoresist composition of Example 1-2 and Comparative Example 1-2

[0105] Components Example 1 Example 2 Comparative Example 1 Comparative Example 2 Polymer-1 (parts by mass) 80 Polymer-2 (parts by mass) 80 Polymer-3 (parts by mass) 80 Polymer-4 (parts by mass) 80 PAG (parts by mass) 10 10 10 10 Crosslinking agent (parts by mass) 8.2 8.2 8.2 8.2 Quencher-1 (parts by mass) 0.1 0.1 0.1 0.1 Quencher-2 (parts by mass) 0.1 0.1 0.1 0.1 Surfactant (parts by mass) 0.07 0.07 0.07 0.07 Solvent A (parts by mass) 800 800 800 800 Solvent B (parts by mass) 1800 1800 1800 1800

[0106] Application Example 1-2 and Comparative Application Example 1-2

[0107] The negative photoresist compositions obtained in Examples 1-2 and Comparative Examples 1-2 were filtered with a 0.04 μm filter made of nylon resin, and then each photoresist solution was spin-coated at 1700 rpm onto a substrate having a chromium oxynitride film on the outermost surface, so that the coating thickness was 90 nm. Next, each mask was baked on a heating plate at 110° C. for 10 minutes, then exposed using an electron beam exposure device (NuFLARE Technology, Inc., EBM5000 accelerating voltage 50 keV), then baked at 120° C. for 10 minutes, and then spray developed using a 2.38% tetramethylammonium hydroxide aqueous solution to obtain a negative film pattern.

[0108] Among them, Application Example 1 uses the negative photoresist composition of Example 1, Application Example 2 uses the negative photoresist composition of Example 2, Comparative Application Example 1 uses the negative photoresist composition of Comparative Example 1, and Comparative Application Example 2 uses the negative photoresist composition of Comparative Example 2.

[0109] The negative film patterns obtained in Example 1-2 and Comparative Application Example 1-2 were evaluated as follows.

[0110] Assuming that the exposure dose for distinguishing the top and bottom of the 200nm line and space pattern at a resolution of 1:1 is the optimal exposure dose (sensitivity: Eop), the minimum line width of the separated line and space pattern found at this exposure dose is defined as the resolution suitable for evaluating the photoresist. In addition, the profile of each resolved negative photoresist pattern is observed at the cross section of the resist using a scanning electron microscope, and in particular, the presence or absence of undercut at the substrate side boundary surface of the photoresist is observed. Each photoresist is actually etched using the device TE-8500S manufactured by Tokyo Electron Co., Ltd., and then the pattern profile of the photoresist cross section is observed using a scanning electron microscope. When the film thickness reduction of Comparative Example 1 after etching is 1.0, the relative ratio of the reduction in its photoresist is used to represent the etching resistance of each negative photoresist composition. That is, the smaller the value, the stronger the etching resistance of the negative photoresist composition. The performance test results of the negative film patterns obtained by Application Example 1-2 and Comparative Application Example 1-2 are shown in Table 2.

[0111] Table 2 Performance test table of negative film patterns obtained from application examples 1-2 and comparative application examples 1-2

[0112]

[0113] It can be seen from Table 2 that, compared with comparative application examples 1-2, application examples 1-2 have lower resolution and lower sensitivity, indicating that the present application scheme can form a pattern with high sensitivity and high resolution.

[0114] In comparative application example 1, a polymer comprising 4-hydroxystyrene units (the first repeating unit, wherein m=1) and 4-chlorostyrene units (the second repeating unit, wherein X is an electron withdrawing group, specifically chlorine, and n=1) is used as the polymer. Due to the presence of bridging, a 70nm pattern cannot be developed.

[0115] In Comparative Application Example 2, compared with the polymer used in Comparative Application Example 1, the polymer of Comparative Application Example 2 further includes an indene unit (the third repeating unit), and Comparative Application Example 2 can obtain a pattern of 60 nm.

[0116] The chlorostyrene unit (the second repeating unit, wherein X is an electron withdrawing group, specifically chlorine, and n=1) used in Comparative Application Examples 1 and 2 has a low crosslinking efficiency and a very low sensitivity of only 35 μC.

[0117] In Application Example 1 and Application Example 2, a polymer containing a styrene unit (4-methoxystyrene) substituted with an electron donor group is used, and the cross-linking efficiency is high and the sensitivity is 13μC. Moreover, in Application Example 1 and Application Example 2, each pattern of 45nm or less has no undercut or bridging. In addition, each pattern obtained in Application Example 2 has a higher resolution than each pattern obtained in Application Example 1. This is due to the difference between the polymers in Application Example 1 and Application Example 2. The polymer in Application Example 1 includes an indene unit (the third repeating unit), and the polymer in Application Example 2 includes an acenaphthene unit (the fourth repeating unit). The resolution of Application Example 1 is greater than that of Application Example 2. This is because the polymer containing the acenaphthene unit has greater rigidity, which can inhibit pattern deformation during the development process.

[0118] Regarding etching resistance, in Comparative Application Example 2, the film thickness reduction after etching is 0.9 times. The polymer used in Application Example 1 is a polymer in which the 4-chlorostyrene repeating unit in the polymer of Comparative Application Example 2 is replaced with a 4-methoxystyrene repeating unit, and the film thickness reduction after etching in Application Example 1 is 0.8 times. Therefore, it is proved that the chlorine group will reduce the etching resistance. The polymer used in Application Example 2 is a polymer in which the indene repeating unit in the polymer of Application Example 1 is replaced with an acenaphthene repeating unit, and the film thickness reduction after etching in Application Example 2 is 0.7 times compared with Comparative Application Example 1, so it can be seen that the acenaphthene unit has excellent etching resistance.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0120] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A negative photoresist composition, characterized in that The negative photoresist composition comprises a polymer, wherein the polymer comprises a first repeating unit represented by formula (1) and a second repeating unit represented by formula (2); wherein m and n are independently selected from integers of 1 to 4, and X comprises an electron donating group.

2. The negative photoresist composition according to claim 1, characterized in that Each of the Xs is independently selected from any one of a hydrogen atom, a linear alkyl group, a branched alkyl group or a cyclic alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms; Preferably, each X is independently selected from any one of methyl, ethyl, methoxy and ethoxy.

3. The negative photoresist composition according to claim 1, characterized in that: The polymer further comprises a third repeating unit represented by formula (3); The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the third repeating unit in the polymer is 8% to 12%.

4. The negative photoresist composition according to claim 1, characterized in that The polymer further comprises a fourth repeating unit represented by formula (4); The molar proportion of the first repeating unit in the polymer is 73% to 80%, the molar proportion of the second repeating unit in the polymer is 10% to 15%, and the molar proportion of the fourth repeating unit in the polymer is 8% to 12%.

5. The negative photoresist composition according to claim 1, characterized in that: The weight average molecular weight of the polymer is 1,000 to 10,000.

6. The negative photoresist composition according to any one of claims 1 to 5, characterized in that: The negative photoresist composition further comprises an acid generator, a carboxyl-containing amine compound, a crosslinking agent, a surfactant, and a solvent, wherein the nitrogen atom in the carboxyl-containing amine compound is not connected to a hydrogen atom.

7. The negative photoresist composition according to claim 6, characterized in that: The acid generator includes triphenylsulfonium-2,4,6-triisopropylbenzenesulfonate; The carboxyl-containing amine compounds include p-diethylaminobenzoic acid and 1-piperidinylpropionic acid; The cross-linking agent includes tetramethoxymethyl glycoluril; The surfactant includes PF-636; The solvents include ethyl lactate and propylene glycol methyl ether acetate.

8. The negative photoresist composition according to claim 7, characterized in that: In the negative photoresist composition, the mass ratio of the polymer to the acid generator is 80:(8-12), the mass ratio of the polymer to the p-diethylaminobenzoic acid is 80:(0.05-0.15), the mass ratio of the polymer to the 1-piperidinepropionic acid is 80:(0.05-0.15), the mass ratio of the polymer to the cross-linking agent is 80:(6-10), the mass ratio of the polymer to the surfactant is 80:(0.05-0.09), and the mass ratio of the polymer to the solvent is 80:(2400-2800).

9. A patterning method, characterized in that: include: Applying the negative photoresist composition according to any one of claims 1 to 8 on a substrate to be processed to form a negative photoresist layer; performing an exposure process on the negative photoresist layer; The negative photoresist layer subjected to the exposure treatment is developed to obtain a resist pattern.

10. The patterning method according to claim 9, characterized in that: The thickness of the negative photoresist layer is 10-100 nm; And / or, the substrate to be processed includes a photomask blank, and the outer surface material of the photomask blank includes a chromium-containing compound.

Citation Information

Patent Citations

  • Chemically amplified negative resist composition and patterning process

    CN101387831A

  • Negative resist composition and patterning process using the same

    CN101900939A